STUDY OF THE PERFORMANCE CHARACTERISTICS OF UNIVERSAL MONOCRYSTALLINE PHOTOELECTRIC CONVERTERS UNDER VARIOUS LIGHTING CONDITIONS - Габринець, Володимир; Накашидзе, Лілія (SWorldJournal, 2025)
The paper experimentally investigates three types of modern monocrystalline silicon photovoltaic solar energy converters, which can be used both in Space and on Earth under different lighting conditions. The data obtained determine the influence of the or